Difusa ou especular? Estudando o desempenho da prateleira de luz segundo a refletância de sua superfície - Manhas, Max Paulo Giacheto (2016)
Light is one of the most important elements for seizure of the architectural space and can be considered the most valuable resource by the architect, responsible for biological effects, psychological and human visual system. You can also reduce the use of artificial lighting systems, contributing to the growing global awareness of the depletion of natural resources of the planet. However, its use in architecture should be made based on criteria in order to optimize its benefits. Thus, the light shelf can be used as a daylighting control element, which reduces the direct incidence of sunlight, can more evenly distribute light within the room. Using computer simulation software TropLux proceeded to the simulation of a basic room with no light shelf and weather data for the city of Maceio. From there, nine other rooms were created with light shelf and each received a different reflectance configuration of 0.9, 0.7 and 0.5, ranging from diffuse, specular and mixed. the values were compared between the standard room and the other as well as between the points of the same depth between the different rooms in order to establish which setting has allowed a better light performance. As a result, we arrived at the conclusion that the use of light shelf to fully diffuse surface, provided a greater uniformity in the distribution of natural lighting within the environment in comparison to the use of mixed or specular surfaces. The light shelves with reflectance of 0.5 in comparison to others, showed better uniformity of illuminance.